Implementation of the Alliance for Innovation on Maternal Health Program to Reduce Maternal Mortality in Malawi. Issue 3 (March 2019) - Chang, Olivia H.; Levy, Barbara; Lytle, Heather; Pope, Rachel; Phiri, Henry; Gellhaus, Thomas; Eckhardt, Carla; Sclafani, Joseph
Abstract : OBJECTIVE: To evaluate maternal mortality and changes in the culture of safety before and after the implementation of the Alliance for Innovation on Maternal Health (AIM) Malawi program. METHODS: This was a prospective cohort study at a central hospital and a district health center in Malawi from March 2016 to November 2017. The AIM Malawi program included classroom didactics on obstetric hemorrhage, teamwork protocols, skills laboratory activities, and simulation training. The time periods of comparison were preintervention, education period, and postintervention. Hospital birth paper records were used to collect data on patient demographics and obstetric and neonatal information. The Hospital Survey of Patient Safety was used to measure the culture of safety before and after the program. RESULTS: We trained 128 participants. In the postintervention period, 16 procedural interventions were performed to manage postpartum hemorrhage, including B-lynch sutures (n=7), condom balloon catheter (n=5), nonpneumatic antishock garment (n=3), and uterine artery ligation (n=1). There was a significant increase in the use of B-lynch sutures for the management of uterine atony in the postintervention compared with preintervention period ( P =.014). In the postintervention period, the rate of maternal mortality from obstetric hemorrhage decreased significantly from 1.2% to 0.2% ( P =.02), a relative decrease of 82.1% from the preintervention rate. Hospital safety culture scores improved significantly from baseline in four out of five domains after the AIM Malawi training. CONCLUSION: After implementation of the AIM Malawi program, we found an increased use of postpartum hemorrhage procedural interventions, a decreased rate of maternal mortality and an increase in Hospital Survey of Patient Safety composite safety scores. The AIM Malawi program may be an effective framework for adaptation to improve maternal mortality in a low-resource setting. Abstract : The Alliance for Innovation on Maternal Health Program used procedural interventions, obstetric bundles, and team training to reduce maternal mortality from obstetric hemorrhage and improve safety culture in Malawi.